Immunohistological Analysis of the Jun Family and the Signal Transducers and Activators of Transcription in Thymus - Papoudou-Bai, Alexandra (Anat Res Int, 2015)
The Jun family and the signal transducers and activators of transcription (STAT) are involved in proliferation and apoptosis. Moreover, c-Jun and STAT3 cooperate to regulate apoptosis. Therefore, we used double immunostaining to investigate the immunotopographical distribution of phospho-c-Jun (p-c-Jun), JunB, JunD, p-STAT3, p-STAT5, and p-STAT6 in human thymus. JunD was frequently expressed by thymocytes with higher expression in medullary compared to cortical thymocytes. p-c-Jun was frequently expressed by cortical and medullary thymic epithelial cells (TEC) and Hassall bodies (HB). p-STAT3 was frequently expressed by TEC with higher expression in cortical compared to medullary TEC and HB. p-c-Jun, JunB, p-STAT3, p-STAT5, and p-STAT6 were rarely expressed by thymocytes. JunB and JunD were expressed by rare cortical TEC with higher expression in medullary TEC. p-STAT5 and p-STAT6 were expressed by rare cortical and medullary TEC. Double immunostaining revealed p-c-Jun and JunD expression in rare CD11c positive dendritic cells. Our findings suggest a notable implication of JunD in the physiology of thymocytes and p-c-Jun and p-STAT3 in the physiology of TEC. The diversity of the immunotopographical distribution and the expression levels of p-c-Jun, JunB, JunD, p-STAT3, p-STAT5, and p-STAT6 indicates that they are differentially involved in the differentiation of TEC, thymocytes, and dendritic cells.